PP.01.37: DELETERIOUS EFFECTS OF COLD AIR INHALATION DURING EXERCISE IN CORONARY ARTERY DISEASE PATIENTS. (June 2015) - Williams, R.; Harwood, A.; Fok, H.; Gu, H.; Jiang, B.; Lumley, M.; Arri, S.; Chowienczyk, P.; Marber, M.; Redwood, S.; Clark, J.
Abstract : Objective: Shovelling snow is the biggest cause of exertion-related cardiac death, involving isometric and dynamic exercise. However, mechanisms underlying deleterious effects of cold air inhalation (CAH) during different exercise stressors are poorly understood. We measured haemodynamic responses to handgrip and cycling in coronary artery disease (CAD) patients,  ± CAH, to assess the effect of CAH on afterload. Design and method: Eight subcritical CAD patients (62 ± 9 yrs) underwent randomized stressors: -15oC cold air (CAH) or room air (RAH) inhalation for 5 minutes, combined with handgrip (30% maximal voluntary contraction) or cycling with an incremental work load for 5 minutes. Carotid pulse wave analysis and echocardiography were performed at peak stress. Heart rate (HR), mean arterial pressure (MAP), and systemic vascular resistance (SVR) were calculated. P1, P2, augmentation pressure (AP) and Buckberg Index (BI) were derived using custom software. A lower BI ratio indicates increased risk of myocardial ischaemia. Data presented as mean ± SD. Results: CAH significantly reduced BI when combined with either handgrip or cycling. CAH, compared to RAH, increased afterload (MAP) when combined with handgrip (115.8 ± 22.4vs130.8 ± 26.7mmHg, p<0.001), but not when combined with cycling (117.2 ± 16.8vs119.5 ± 18.9mmHg, p = NS). P2 and AP, which are closely associated with myocardial contractility, increased with CAH during handgrip exercise but not during cycling. However CAH only caused a significant increase in HR when combined with cycling (130 ± 9.7vs140 ± 10.1bpm, p < 0.05). SVR decreased with cycling and increased with handgrip during RAH. CAH did not change SVR during handgrip or cycling. There were no significant differences between baseline measurements and RAH at rest. Figure. No caption available. Conclusions: This study shows, for the first time, that CAH significantly increases myocardial oxygen demand and the risk of myocardial ischaemia during isometric or dynamic exercise. However the mechanisms appear to be distinct. CAH likely causes an increase in sympathetic drive, which when combined with isometric exercise results in steady state (afterload) and pulsatile increases in arterial pressure, the latter being driven by increases in myocardial contractility. Yet dynamic exercise results in a sufficient reduction in SVR to override any increased resistance caused by CAH, with the principal determinant for increased myocardial oxygen demand being an increase in HR.